2017
DOI: 10.1080/09602011.2016.1273119
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of home-based visuomotor feedback training in stroke patients with chronic hemispatial neglect

Abstract: Hemispatial neglect is a severe cognitive condition frequently observed after a stroke, associated with unawareness of one side of space, disability and poor long-term outcome. Visuomotor feedback training (VFT) is a neglect rehabilitation technique that involves a simple, inexpensive and feasible training of grasping-to-lift rods at the centre. We compared the immediate and long-term effects of VFT vs. a control training when delivered in a home-based setting. Twenty participants were randomly allocated to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 99 publications
1
21
0
7
Order By: Relevance
“…However, he showed surprising visuomotor competence, as reflected by his ability to orient and shape his hand for reaching and grasping objects. The authors concluded that the preservation of the visuomotor sensitivity is mediated by the residual dorsal pathway (Goodale and Milner, 1992), consistent with findings that the magnocellular-dorsal pathway supports residual visual perception functions for action (although see Rossit et al, 2017, for some recent counter-evidence).…”
Section: Plasticity In Higher-order Visual Cortexsupporting
confidence: 59%
“…However, he showed surprising visuomotor competence, as reflected by his ability to orient and shape his hand for reaching and grasping objects. The authors concluded that the preservation of the visuomotor sensitivity is mediated by the residual dorsal pathway (Goodale and Milner, 1992), consistent with findings that the magnocellular-dorsal pathway supports residual visual perception functions for action (although see Rossit et al, 2017, for some recent counter-evidence).…”
Section: Plasticity In Higher-order Visual Cortexsupporting
confidence: 59%
“…This study highlighted the effectiveness of VFT which has been neglected in the rehabilitation field [ 27 ]. However, it showed large effect sizes in both mental function and, activity and participation even though the selected study had only a 2 week intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…All participants trialled a novel VR version of our home-based therapy for spatial neglect (Rossit et al, 2019) -computerized spatial inattention grasping home-based therapy (C-SIGHT - Figure 1A). During the focus group, the stroke survivors and carers also trialled three VirtualRehab 'exergames' (videogame-like exercise activities developed by Evolv Rehabilitation Technologies) including: 'Boxing' (sparring with a virtual boxing partner; Figure 1B), 'Bullseyes and Barriers' (hitting or avoiding targets; Figure 1C) and 'In the Kitchen' (search task in realistic kitchen layout; Figure 1D).…”
Section: Self-administered Vr Telerehabilitationmentioning
confidence: 99%
“…None of the stroke survivors received any form of spatial neglect rehabilitation at the time of this study. Prior to focus groups, spatial neglect was formally assessed in a separate session at the participant’s home, using paper-and-pencil tests including Behavioural Inattention Test (BIT; Wilson, Cockburn & Halligan, 1987), line bisection task (Rossit et al, 2019) and the paper version of the Broken hearts test (Oxford Cognitive Screening; Demeyere et al, 2015). Five stroke survivors were classified as having chronic neglect at the time of the study (N+) as they were impaired in at least one of the spatial neglect tests ( n = 3 left side neglect, n = 2 right side neglect).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation